Seeing and Experiencing Chouinard: The Body Language of the Spectator - Cornell, Katherine (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractThis article employs Julia Kristeva’s concept of the chora as a means to describe and analyze the dancing body and the body of the spectator. In Revolution in Poetic Language, Kristeva posits the chora as analogous to vocal and kinetic rhythms of the body. As an audience member who also trained as a dancer, I find my body responds instantaneously and rhythmically to dance performances, thereby connecting to the chora. Subsequently, the act of writing becomes a physical manifestation of the theatrical experience. My research questions include: what role does the body play in the transmission of dance to language? How is the essence of the chora transferred from dancer to spectator in the experience of watching a performance? The writings of Julia Kristeva, Roland Barthes and John Martin provide important theories of the body that aid in answering these research questions. With an awareness of the chora in each subject, I examine the transfer of the chora from the dancer to the spectator in the work of Montréal choreographer Marie Chouinard, specifically the male solo Des feux dans la nuit. Marie Chouinard stands out as one of Canada’s most successful and internationally recognized contemporary choreographers. This article considers the impact of Chouinard’s dancing body on the spectator.